Identification of critical success factors that maximise customers’ satisfaction: multivariate analysis - Hélder Pires Ferreira; Paula Odete Fernandes (Tourism & Management Studies)
This study was based on the identification of critical success factors (CSFs) that maximise customer satisfaction, as well as an analysis of customers’ degree of satisfaction and the importance that they attach to CSFs. For this purpose, 225 customers of the company Futurlab were surveyed, with a sampling error of 5.8% at a significance level of 5%. To identify the CSFs, we used exploratory factor analysis and, to analyse satisfaction and importance for the CSFs, we used an importance-satisfaction matrix. This study also sought to identify homogeneous groups of customers using cluster analysis. Based on the results, seven CSFs were identified, and, in general, customers showed satisfaction with the performance of Futurlab. The cluster analysis identified four clusters according to the importance and satisfaction attributed to the CSFs.